2014
DOI: 10.1111/jcmm.12198
|View full text |Cite
|
Sign up to set email alerts
|

Regional mapping of myocardial hibernation phenotype in idiopathic end‐stage dilated cardiomyopathy

Abstract: Myocardial hibernation (MH) is a well-known feature of human ischaemic cardiomyopathy (ICM), whereas its presence in human idiopathic dilated cardiomyopathy (DCM) is still controversial. We investigated the histological and molecular features of MH in left ventricle (LV) regions of failing DCM or ICM hearts. We examined failing hearts from DCM (n = 11; 41.9 ± 5.45 years; left ventricle-ejection fraction (LV-EF), 18 ± 3.16%) and ICM patients (n = 12; 58.08 ± 1.7 years; LVEF, 21.5 ± 6.08%) undergoing cardiac tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 58 publications
7
34
0
Order By: Relevance
“…We have detected larger myocardial deposits of type I collagen, fibronectin and fibroblasts in ICM rather than DCM hearts [31], in accord with previous studies [34][35][36][37][38]. Our data are also consistent with proteomic analysis performed by us on the same LV samples [31], which show the up-regulation of pro-apoptotic and pro-fibrotic factors in ICM failing hearts with overt fibrosis (ICM). In addition, we argue that the proteolytic cleavage of OPN-a in DCM samples may be independent on thrombin, which levels are similarly increased to those of OPN-a.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have detected larger myocardial deposits of type I collagen, fibronectin and fibroblasts in ICM rather than DCM hearts [31], in accord with previous studies [34][35][36][37][38]. Our data are also consistent with proteomic analysis performed by us on the same LV samples [31], which show the up-regulation of pro-apoptotic and pro-fibrotic factors in ICM failing hearts with overt fibrosis (ICM). In addition, we argue that the proteolytic cleavage of OPN-a in DCM samples may be independent on thrombin, which levels are similarly increased to those of OPN-a.…”
Section: Discussionsupporting
confidence: 82%
“…Cathepsin D, an aspartyl lysosomal protease, is able to cleave OPN-a at the level of RGD domain [40], an arginine-glycine-aspartic acid domain that is also recognized by thrombin and plasmin [40], cell surface integrins expressed by fibroblasts [41] or non-RGD integrins, such as α4β1 and α9β1 [3,42,43]. In our samples, the LV cathepsin-D expression was up-regulated in ICM rather than DCM failing hearts [31]. The above mentioned proteomic findings well support the detection of higher levels of OPN-a in the presence of higher thrombin levels in our DCM failing hearts.…”
Section: Discussionmentioning
confidence: 75%
“…Haemodynamic measurements showed decreased contractility without a significant increase in the ventricular filling pressures. Previous studies have suggested that mechanical dyssynchrony, in the absence of coronary stenosis, can cause myocardial hibernation . Therefore, we tested the presence of molecular mechanisms associated to myocardial hibernation in our in vivo model.…”
Section: Resultsmentioning
confidence: 99%
“…Reports about HM in cases of cardiomyopathies, a diabetic cardiomyopathy [8] and idiopathic dilated one (DCMP) [9] indeed appeared recently. However there are no reports about HM in cases of neuroleptic cardiomyopathy (NCMP) in literature although NCMP belongs to specific (secondary) DCMP's [10] as well as ICMP, but HM is quite often observed in cases of ICMP [6].…”
Section: Introductionmentioning
confidence: 99%